The Principles and the Teaching of English Vocabulary: A Review - Dakhi, Saniago; Fitria, Tira Nur (JET (Journal of English Teaching), 2019)
The importance of vocabulary, its types, selection criteria, size and depth, and teaching principles were found unclear. The present article seeks to respond to such challenge. To achieve the mentioned goals, we did a systematic review to previously related studies and theories. The results showed that the vocabulary was found to be more functional as a basis for communication, a reflection of social reality, emotion booster, and academic ability predictor. It also revealed that its contribution to the basic language skills varied. Finally, the principles of teaching vocabulary, size and depth, and teaching and learning vocabulary materials (TLVMs) appeared to be associated with student’s vocabulary mastery. Keywords: vocabulary teaching; principles; vocabulary importance; breadth and depth